Optimizing live streaming features to enhance customer immersion and engagement: A comparative study of live streaming genres in China - Tian, Yu; Frank, Björn (Journal of retailing and consumer services, 2024)
Based on the flow theory, this study examines how influencer characteristics and live streaming features (interactivity, utility, entertainment, and harmony) affect the viewer's flow experience (i.e., immersion) and engagement behavior (e.g., purchasing, gifting) across different live streaming genres (utilitarian vs. hedonic, high vs. low involvement; a 2 × 2 between-subjects design). As extensions of the literature, it focuses on live streaming features (rather than merely the influencer), the mediating effect of flow experience, and differences across live streaming genres. Analysis of data from 1233 Chinese live streaming users shows that interactivity, utility, and entertainment (but not harmony) stimulate the viewer's flow experience, which mediates their effects on monetary and non-monetary engagement behaviors. Contrary to intuition, since flow experiences require a balance of utility and entertainment, influencers need to emphasize utility in hedonic live streaming genres and entertainment in utilitarian genres. Utility is more important and interactivity is less important in high-involvement and hedonic genres. Regarding influencer characteristics, trustworthiness, expertise, and charisma positively influence the flow experience. As a contribution to the live streaming literature, this study explains how live streaming features can be optimized to improve customer engagement. [Display omitted] •Live streaming features affect viewers' customer engagement behavior.•These effects differ by genre (utilitarian vs. hedonic content; involvement level).•Interactivity, utility, and entertainment are effective features, but not harmony.•A viewer's flow (i.e., immersion) experience mediates the effects on engagement.•Flow affects both monetary (e.g., gifting, purchasing) and non-monetary engagement.